2011
DOI: 10.1038/aja.2010.183
|View full text |Cite
|
Sign up to set email alerts
|

The role of antioxidant therapy in the treatment of male infertility: an overview

Abstract: In recent years, many studies have focused on the effect of oxidative stress, reactive oxygen species (ROS) and antioxidants on the male eproductive system. Under physiological conditions, sperm produces small amounts of ROS, which are needed for fertilisation, acrosome reaction and capacitation. However, if an increased production of ROS is not associated with a similar increase in scavenging systems, peroxidative damage of the sperm plasma membrane and loss of DNA integrity typically occur, which leads to ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
76
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 81 publications
(149 reference statements)
2
76
2
2
Order By: Relevance
“…[33] In normal conditions, ROS expression plays physiological roles in cellular differentiation, sperm capacitation, acrosome reaction, and maintenance of fertilizing ability, whereas oxygen free radicals at concentrations beyond physiological limits result in oxidative stress. [34,35] ROS overexpression secondary to oxidative stress can negatively affect proteins, lipids, nucleic acids, carbohydrates, and other molecules and leads to cell membrane lipid peroxidation, protein denaturation, DNA damage, inflammation, cell proliferation, cell dysfunction, and apoptosis. [36] Thus, ROS may play a role in the pathogenesis of several diseases, such as atherosclerosis, [37] cancer, [38] diabetes mellitus, [39] infection, [40] central nervous system disorders, [41] and testicular torsion due to its involvement in lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…[33] In normal conditions, ROS expression plays physiological roles in cellular differentiation, sperm capacitation, acrosome reaction, and maintenance of fertilizing ability, whereas oxygen free radicals at concentrations beyond physiological limits result in oxidative stress. [34,35] ROS overexpression secondary to oxidative stress can negatively affect proteins, lipids, nucleic acids, carbohydrates, and other molecules and leads to cell membrane lipid peroxidation, protein denaturation, DNA damage, inflammation, cell proliferation, cell dysfunction, and apoptosis. [36] Thus, ROS may play a role in the pathogenesis of several diseases, such as atherosclerosis, [37] cancer, [38] diabetes mellitus, [39] infection, [40] central nervous system disorders, [41] and testicular torsion due to its involvement in lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 Recently, studies have focused on assessing the effectiveness of in vivo and in vitro supplementation with different antioxidants in an attempt to protect spermatozoa exposed to oxidative stress. [10][11][12][13][14] A beneficial effect of the in vitro supplementation of different natural or chemically synthesized antioxidant compounds on human spermatozoa has been observed; however, their effect has also been shown to decrease at inadequate concentrations and, even worse, to behave as pro-oxidants. 11,12,15,16 Herein, we discuss the protective role of exogenous gangliosides against ROS-induced changes based on our studies of human spermatozoa, leukocytes and cell-free systems.…”
Section: Introductionmentioning
confidence: 99%
“…Our study suggest that the DM might reduce the cholesterol levels of the plasma membrane because of its increasing effect on the ROS quantity within the cauda epididymis, so it might enhance the number of spermatozoa having undergone the premature AR. Lombardo et al [56] noted that the reduction in ROS concentration by using antioxidants exerts adverse effect on male fertility. Some studies indicated that when antioxidants are used in oral pills and/or added directly into ejaculated spermatozoa, the rate of spermatozoa having undergone the AR increases [57,58] .…”
Section: Discussionmentioning
confidence: 99%